Development of Perceived Psychological Contract Violations (PPCV): A Theoretical Study - Ahuja , Sanya (Gyan Management Journal, 2023)
In order to survive in this constantly changing and transforming environment, a business requires agility and a rapid response technique. One heuristic technique that can be focused upon to embrace the said change and bring about a transformation is the understanding of psychological contracts as well as their violations. Psychological contracts are “intangible” contracts that exist at a place of work. Perceived Psychological Contract Violations (PPCV) is a concept that helps to identify and explain the feeling of anger and disappointment that employees face when their needs are not met by the employer. PPCV has two types – Reneging and Incongruence. The purpose of this paper is to develop a theoretical study indicating the identification and development of psychological contracts at the workplace, the subsequently developed perceived psychological contract violations (PPCV), as well as to further explain their types. Efforts have been made to present a thorough study of literature and to brief the results of the same so that there is a better understanding of the given terms. Findings and implications of this framework have been discussed in detail and suggestions for further research have been given.